The impact of big data analytics on financial statement auditing: an exploratory study - Gurbachan Singh, Mangehna Kaur (2021)
The audit industry has been largely affected by the evolvement of technology over the years and accordingly, it has imposed challenges on audit firms and auditors. Several studies investigated the impact of information technology (IT), in terms of the extent of which the IT audit techniques have been used, but very few studies are available based on the transition from conventional audit to technology based audit in developing countries. This study focusses on exploring the impact of implementing Big Data Analytics (BDA) in the Big- Five audit firms in Malaysia – a developing country. There are three objectives of this study. (1) To investigate the changes from traditional auditing to auditing with the presence of BDA. (2) To determine the primary challenges auditors and audit firms face when implementing and sustaining the use of BDA in their respective audit firms. (3) To analyze how is BDA helping auditors provide better quality audit.